Pola Respirasi dan Senyawa Flavor Selama Tahap Pemasakan Buah Salak Pondoh - Tranggono Tranggono (agriTECH, 1998)
Studies on respiration pattern and flavor compound changes 'during maturation stage in the development of snake fruit (Salacca edulrs Reinw cultivar Pondoh) were carried out at picking times of 4.5, 5.0, 5.5, 6.0 and 6.5 months after pollination. At each time, samples were drawn for determinations of edible portion, moisture; respiration rate, ester and carbonyl compounds as well as their flavor profiles by gas liquid chromatography. Result showed that the development of maturation degree gives rise to an increase in the relative percentage of edible portions. The snake fruit displayed a non-climacteric pattern of respiration. During maturation stage from 4.5 until 6:5 months after pollination, the fruits exhibited a decrease in ester and an increase in carbonyl compounds. However, fruits picked at 6.5 months after pollination revealed an additional in respiration rate as well as ester content and a diminishing in carbonyl compounds. These may be due to stress condition caused by initial break down of edible tissues. Flavor profile chromatograms which were obtained from head space analyses, showed that changes in volatile compounds in term of type and their relative percentages occur during maturation.